Thermal analysis of the W/Cu flat-type component used as lower divertor target in EAST - Chunyu He; Dahuan Zhu; Baoguo Wang; Changjun Li; Binfu Gao; Yang Wang; Yi Li; Chuannan Xuan; Wenxue Fu; Rong Yan; Guoliang Xu; Rui Ding; et al. (Nuclear Materials and Energy)
The tungsten-copper (W/Cu) flat-type component is a promising candidate for plasma-facing components, praised for its flexible heat sink design and cost-effective fabrication. It is considered for the ITER divertor dome section and holds potential for divertor targets for future fusion devices. Since 2021, three types of ITER-like W/Cu flat-type components with chamfer angles of 2.40°, 3.76°, and 5.19° have been installed and tested on the outer horizontal target of the lower divertor in EAST. During plasma operations, some W/Cu flat-type components experienced cracking, melting and exfoliation of tungsten, causing plasma disruptions and even the termination of experiments. To address this, this study uses Fluent to evaluate the melting thresholds of these components based on simulations that consider actual conditions. The key findings are summarized: Firstly, only certain W plates can reach high temperatures because the in-situ heat flux is localized, explaining why damage often occurs only on some specific plates. During leading-edge events, the highest temperatures for both W and oxygen-free copper (OFC) occur near the sides, but W’s maximum temperature is at the edge, while OFC’s is near the edge. The high-temperature area for OFC is larger than that for W, resulting in a more uniform temperature distribution. Secondly, for components with chamfer angles of 3.76° and 5.19°, the heat flux q0 required for OFC to melt is always lower than that for W, meaning OFC melts first. For the 2.40° chamfer, OFC melts first when the incident heat flux angle exceeds 2.5°, while W melts first below this angle. At a 10 MW total heating power, all three components face a melting risk at the maximum incident angle of 5° during EAST operations. Thirdly, a linear relationship was identified between the maximum temperatures of W and OFC under such complex loading conditions, offering a method for monitoring OFC maximum temperature based on the IR measurement of surface W temperature. Moreover, this linear relationship can be extended to other heat sink materials. These results provide valuable guidance for EAST’s plasma operations and offer reference data for the use of W/Cu flat-type components in next-generation devices like ITER and CFETR.